Rapid Micro‐Induction of Buprenorphine/Naloxone for Opioid Use Disorder in an Inpatient Setting: A Case Series. Issue 4 (22nd March 2019) - Klaire, Sukhpreet; Zivanovic, Rebecca; Barbic, Skye Pamela; Sandhu, Raman; Mathew, Nickie; Azar, Pouya
Abstract : Background and Objectives: Buprenorphine/naloxone has been shown to be effective in the treatment of opioid use disorder. Due to its pharmacological properties, induction can be challenging, time‐consuming, and result in sudden onset of withdrawal symptoms. Methods: Retrospective case series ( n = 2). Results: Two patients with opioid use disorder were successfully started on buprenorphine/naloxone using a rapid micro‐induction technique that did not cause precipitated withdrawal or require preceding cessation of other opioids. Discussion and Conclusions: These cases provide an alternative method for starting buprenorphine/naloxone that offers unique benefits compared to protocols previously described in the literature. Scientific Significance: This method can be used to minimize barriers to opioid agonist therapy. (Am J Addict 2019;28:262–265)